EVALUATION OF PHYSICAL-CHEMICAL VARIABLES AND HEAVY METAL CONCENTRATIONS OF SEAWATER SAMPLES IN RECREATIONAL BEACHES IN COSTA RICA - Bermúdez-Kuminev, Fernando (2025)
Costa Rica has a legal gap in terms of the regulations to control the seawater quality in recreational beaches, so the present investigation aimed to create a exploratory study of heavy metals concentrations in recreational beaches in Costa Rica. In 2013, a monitoring campaign was carried out on thirteen beaches on the Pacific coast, and five beaches on the Caribbean coast. The country was divided into four zones North Pacific (PN), Central Pacific (PC), South Pacific (PS) and Southern Caribbean (CS). Eight heavy metals (Mn, Cd, Co, Fe, Cr, Ni, Cu, Pb) were analyzed in seawater samples by absorption spectrometry, and the physicochemical characteristics (pH and temperature) were measured in situ. The pH was significantly more basic in the PN (P=0. 0001), and a temperature difference of up to 3°C between the Pacific and Caribbean coasts was registered. The PC showed the highest concentrations for metals such as Pb, Cr, and Fe. The highest concentrations of metals such as Pb and Cr were found near river mouths and wastewater discharges, indicating the contributions that water bodies are making and the influence of urban areas. This research achieved to develop a monitoring campaign and found concentration of heavy metals that exceed the limits established by law in other countries such as: Chile, Argentina and Peru, and evidences the need to regulate quality standards in these spaces for the safety of the human health of tourism and the different activities that are developed.